Correlation of electrocardiogram parameters and hemodynamic outcomes in patients with isolated secundum atrial septal defects - Mohammad Refaei; Sunjidatul Islam; Andrew S Mackie; Joseph Atallah (Wolters Kluwer Medknow Publications, 2017)
Objective: The characteristic rSR' pattern in lead V1 on electrocardiogram (ECG) has been described in association with atrial septal defect (ASD) and right ventricular dilation. We aimed to determine if temporal ECG changes can guide a more discriminate and cost-effective screening during follow-up of isolated secundum ASD. Methods: Our study population included all pediatric patients followed at the Stollery Children's Hospital with a secundum ASD, not associated with other significant heart disease, between 2004 and 2010. We collected clinical as well as serial echocardiographic and ECG data. Results: We identified 141 patients with ASD, 95% were asymptomatic and 88% referred for a murmur. Moderate-to-large (>5 mm) ASDs were present in 52%. The prevalence of an rSR' pattern was 26% in the overall cohort and 54% in the large ASD group. During median follow-up of 28.7 months, 37 patients underwent surgical or transcatheter closure. Among patients with rSR' on ECG, 78% had moderate-to-large ASD size. In that group, the presence versus the absence of rSR' correlated with lower positive predictive value (PPV) for spontaneous closure (7% vs. 36%; P = 0.01) and higher PPV for device or surgical closure (71% vs. 38%; P = 0.02). Conclusion: We observed a lower prevalence of rSR' pattern in patients with isolated ASD than previously reported. However, an rSR' pattern had incremental value in predicting the need for surgical or device intervention for closure in moderate.large groups. This can be used to tailor patient echocardiographic screening and caregiver counseling.